The space of opinion media intellectuals and the public sphere - Jacobs, Ronald N.; Townsley, Eleanor R., 1967- (New York ; Oxford : Oxford University Press, 2011)
'The Space of Opinion' describes and analyzes the complex space of commentary and opinion in the news media.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Mass media -- United States -- History -- 21st century; Journalists -- United States -- Attitudes -- History -- 21st century; Public opinion -- United States -- History -- 21st century; United States -- Politics and government -- 21st century